Intelligence platform district power quality comprehensive treatment device braced system based on big data - HAN RONGJIE; WENG LIGUO; LUO HAIFENG; YE JIAN; SHOU JICHAO; QIU HAIFENG; ZHOU JUNWEI; WANG PENGCHENG; FAN HUA; LI NAN; WU ZHENJIE; FENG JUN; et al. (2018)
The utility model relates to a braced system, in particular to intelligence platform district power quality comprehensive treatment device braced system based on big data. Which comprises a bracket body, stake body transversal personally submit the triangle form, a terminal surface of stake body be the equipment locating terminal surface, the equipment locating terminal surface in be equipped withat least a pair of installation waist hole, interval between a pair of installation waist hole is 420~750mm, the length of equipment locating terminal surface be 560~974mm. An intelligence platform district power quality comprehensive treatment device braced system based on big data compact structure, the high intelligentization level is put forward to the lifting operation performance. 本实用新型是种支撑系统，特别涉及种基于大数据的智能台区电能质量综合治理装置支撑系统。包括支架体，所述的支架体的横截面呈三角状，所述的支架体的个端面为设备定位端面，所述的设备定位端面中设有至少对安装腰孔，对安装腰孔间的间距为420～750mm，所述的设备定位端面的长度为560～974mm。种基于大数据的智能台区电能质量综合治理装置支撑系统结构紧凑，提升操作性能，提高智能化水平。